An Application of Holistic Feasibility Study to Determine Valuable Chain in Palm Oil Industry: A Case Study - Wahyudi Sutopo; Dwi Indah Maryanie; Yuniaristanto Yuniaristanto; M. Hisjam (Jurnal METRIS, 2014)
Palm has a good market prospect in the future. Almost all parts of this commodity have their benefits, ranging from the leaves to the roots and from upstream to downstream. However, it would be a big problem to determine the most viable commodity to be developed for hundreds of alternatives derivative palm oil products. This paper aims to present an application to help in deciding between multiple options of derivative products of palm oil. The application is built in Visual Basic Macro within Microsoft Excel (Macro Excel) by using the decision matrix method. It will allow to establish the concept of weighting the criteria in order of importance by scoring them against different criteria. The most important criteria, the higher weighting it will be given. So that the proposed application can be implemented to evaluate which are the most valuable coin from all levels of derivative products in the Palm Oil supply chain.